Proceedings of the Fifth ACM Conference on Recommender Systems 2011
DOI: 10.1145/2043932.2043968
|View full text |Cite
|
Sign up to set email alerts
|

Social link recommendation by learning hidden topics

Abstract: In this paper, a new approach to predicting the structure of a social network without any prior knowledge from the social links is proposed. In absence of links among nodes, we assume there are other information resources associated with the nodes which are called node profiles. The task of link prediction and recommendation from text data is to learn similarities between the nodes and then translate pair-wise similarities into social links. In other words, the process is to convert a similarity matrix into an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
12
1
2
Order By: Relevance
“…Another kind of popular approach utilizes the random walk to measure the node proximity on the whole network [19,2]. Furthermore, matrix factorization methods [27,5], contentbased methods [8,25], attribute-based methods [39] and behavior modeling based methods [41,42,40] have been studied respectively. Supervised methods are also investigated [9,22].…”
Section: Related Workmentioning
confidence: 99%
“…Another kind of popular approach utilizes the random walk to measure the node proximity on the whole network [19,2]. Furthermore, matrix factorization methods [27,5], contentbased methods [8,25], attribute-based methods [39] and behavior modeling based methods [41,42,40] have been studied respectively. Supervised methods are also investigated [9,22].…”
Section: Related Workmentioning
confidence: 99%
“…Makrehchi [2011] constructed a semi-bipartite graph of extracted hidden topics from user profiles and then applied topological metrics such as Katz [Katz 1953] and short path scores to rank and recommend users. Makrehchi [2011] showed that this method outperforms approaches that rely on similarity measures of feature vectors (i.e., Bag of Words) and low rank approximation (i.e., Latent Semantic Indexing (LSI)). We extend this approach by considering resources and metadata to represent users' interests instead of documents consisting of words.…”
Section: Social Link Prediction Using Hidden Topics (Slight)mentioning
confidence: 99%
“…Topic-actor matrix in particular represents a bipartite graph linking topics to actors. Using matrix , we can build a semi-bipartite graph G [Makrehchi 2011] …”
Section: Social Link Prediction Using Hidden Topics (Slight)mentioning
confidence: 99%
See 2 more Smart Citations